Menumbuhkan Sikap Inovatif, Kreatif dan Motif Berprestasi dalam Mendukung Prestasi Kerja Guru (Studi pada Guru SMP Negeri se-Kecamatan Jeumpa, Bireuen – Aceh) - Muhajir, Muhajir; Arief Syarifuddin, Evi; Purnamasari, Purnamasari (peusangan, 2024)
: Schools expect teachers to excel, which in turn will make schools superior. For this reason, it is necessary to develop innovative, creative attitudes and motives to achieve in teachers. This research will examine academically the relationship between these factors. The study was conducted on 118 junior high school teachers in Jeumpa District in Bireuen Regency, Aceh. Using an associative method with statistical analysis. The results found that: 1) factors of innovative, creative attitudes and motivations for achieving teachers will support their work performance, the results of the study recorded 49.45 percent, 40.98 percent, and 62.68 percent respectively. 2) Together, innovative attitudes, creative attitudes and motivations for achieving contribute to shaping teacher work performance by 70,7 percent. 3) And an important note that there is a causal relationship between the variables of innovative attitudes and creative attitudes and motivations for achieving with a fairly high category.